The theoretical and experimental investigation of blank holder forces plate effect in deep drawing process of AL 1050 material - (:unkn) unknown (ELSEVIER SCI LTD, 2008)
The plastic forming process of sheet plate takes an important place in forming metals. The traditional sheet plate forming techniques used in industry are experimental and expensive methods. Prediction of the forming results, determination of the punching force, blank holder forces and the thickness distribution of the sheet metal will decrease the production cost and time of the material to be formed. With this aim, firstly simulation was realized with taking the contact model, material specifications into consideration by using non-linear explicit finite elements method (ANSYS LS-DYNA). In the analysis, the effects of fixed blank holder forces on the wall thickness distribution and wrinkles were examined. As a result of the analysis, without the sheet metal wrinkling or exceeding the tearing limits, for smooth drawings of blank holder the required forces were determined. The results were evaluated and experiments were done with the forces which were determined earlier. As a result of the experiments, which were done with the results obtained with finite elements method, 90% consistency between the experimental and theoretic results was seen. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: FINITE-ELEMENT TECHNIQUES; SIMULATION; CUPS